Freezing and thawing indices in northern Canada - McCormick, G. (Canadian Geotechnical Journal, 1991)
A method for determining the return period of values for thawing and freezing indices is presented. Data are based on published temperature records from 48 weather stations in northern Canada. Key words: freezing, thawing, permafrost.